Factors Influencing Mothers Interest in Choosing IUD Contraception at Biontong Health Center - Rambli Linda Englin Timban; Widia Shofa Ilmiah; Rizful Maulina (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Rapid population growth is a major challenge in Indonesia, despite the ongoing implementation of the Family Planning (KB) program. Among the various contraceptive methods introduced, the Intrauterine Device (IUD) has proven to be an effective long-term solution. However, maternal interest in using the IUD remains relatively low, posing a challenge to achieving optimal family planning outcomes. This study aims to analyze the factors influencing maternal interest in choosing IUDs at Biontong Health Center. The study employed an observational design with a cross-sectional approach. A total of 35 respondents were selected using a total sampling technique. Data were collected through a structured questionnaire that assessed various factors influencing IUD use, including knowledge, gravida status, and previous family planning experience. The results revealed that 57.1% of respondents were not interested in using IUDs, while 42.9% expressed interest. Several significant factors were found to influence maternal interest, particularly the level of knowledge and gravida status. Specifically, respondents with better knowledge about IUDs were more likely to be interested in using them, with 63.6% of those with good knowledge expressing interest, compared to 30.0% with sufficient knowledge and only 35.7% with poor knowledge. Additionally, gravida status also played a significant role, with those who had previous pregnancies showing more interest in IUD use. In conclusion, maternal knowledge and pregnancy experience are key factors influencing interest in IUD use. To increase the adoption of IUDs as a long-term contraceptive option, it is essential to improve education and counseling efforts aimed at increasing public understanding of the benefits and safety of IUDs.